2000
DOI: 10.1093/plankt/22.6.1185
|View full text |Cite
|
Sign up to set email alerts
|

Size-fractionated phytoplankton carboxylase activities in the Indian sector of the Southern Ocean

Abstract: During the ANTARES 3 cruise in the Indian sector of the Southern Ocean in October-November 1995, the surface waters of Kerguelen Islands plume, and the surface and deeper waters (30-60 m) along a transect on 62°E from 48°36ЈS to the ice edge (58°50ЈS), were sampled. The phytoplankton community was size-fractionated (2 µm) and cell numbers, chlorophyll biomass and carbon assimilation, through Rubisco and ␤-carboxylase activities, were characterized. The highest contribution of <2 µm cells to total biomass and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…While our measured PEPC/Rubisco activity ratios are consistent with previous field studies (Bentaleb et al 1998;Fouilland et al 2000), the CO 2 dependence of PEPC activity and PEPC/Rubisco ratios we observed (Fig. 3) is opposite that reported by Reinfelder et al (2000).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…While our measured PEPC/Rubisco activity ratios are consistent with previous field studies (Bentaleb et al 1998;Fouilland et al 2000), the CO 2 dependence of PEPC activity and PEPC/Rubisco ratios we observed (Fig. 3) is opposite that reported by Reinfelder et al (2000).…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, our study is the first to explicitly examine the relationship between CO 2 concentrations and PEPC activity in natural phytoplankton populations. While our measured PEPC/Rubisco activity ratios are consistent with previous field studies (Bentaleb et al 1998;Fouilland et al 2000), the CO 2 dependence of PEPC activity and PEPC/Rubisco ratios we observed (Fig. 3) is opposite that reported by Reinfelder et al (2000).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other studies, measuring extracted Chl, also showed clear and reproducible nighttime maxima for both near surface waters (e.g., [9]) and culture experiments at high light intensities (e.g., [26][27][28][29]). Additionally, Fouilland et al [30] found a depth-dependence of diel variations in Rubisco activity and Chl concentration per cell further supporting a light regime-dependence of Chl profiles.…”
Section: Diel Oscillations Of Chloropigments and Carotenoidsmentioning
confidence: 83%
“…Radioactivity was measured in a Beckman Coulter LS6500 liquid scintillation counter. No correction for dark 14 C uptake was performed, in order to assess the uptake of all autotrophically fixed CO 2 , as high anaplerotic C fixation by phytoplankton may occur in marine surface waters (Fouilland et al 2000;Fouilland et al 2001), and can be enhanced under sudden darkness (Mortain-Bertrand et al 1987). The dissolved inorganic carbon DIC concentrations measured in the samples (Charalampopoulou et al 2008; Tynan Eithne pers comm) were used to calculate the carbon production rates using an isotopic discrimination factor of 1.05.…”
Section: Methodsmentioning
confidence: 99%